Associations between professional time experience and nomenclature adopted in strength training - de Souza, Leonardo Mendes Leal (2016)
Introduction: The divergences of the nomenclature of exercises adopted by physical education teachers in their professional environment can lead to serious communication problems, and consequently interfere in the prescription and the quality of the proposed training. Objective: To associate time of professional experience with the strength training nomenclatures selected by physical education professionals, and identify whether there are differences between the naming frequencies selected for the exercises adopted. Materials and methods: The current study included 191 volunteers. The Chi square test was applied to verify the association of the variables. Results: Significant differences were observed between the nomenclatures options for nine out of ten exercises presented. Nevertheless, there was no association between the responses of nomenclature options with professional experience time in strength training. Conclusion: The present study shows a pattern of names in nine out of ten exercises from physical education professionals independently of their professional experience time.